1976
DOI: 10.1139/b76-082
|View full text |Cite
|
Sign up to set email alerts
|

Some possible sources of error in determining bulk elastic moduli and other parameters from pressure–volume curves of shoots and leaves

Abstract: Pressure–volume curves were constructed from well defined models and hypothetical shoots in which reasonable values of osmotic pressure and cell wall elastic moduli were specified for cell types of different relative volumes. The pressure–volume curves so obtained closely resembled those of real shoots and leaves. Comparing the bulk parameters obtained from analysis of the constructed pressure–volume curves with the values defined in the models allows us to examine the sources of error in their evaluation. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

1979
1979
1996
1996

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 2 publications
2
51
0
Order By: Relevance
“…It should be noted that negative pressures are likely to occur during only extracellular freezing in the cells, hence the use of term L,, in the above expression. However, in many tissues E is not likely to be constant (Cheung et al, 1976) and thus a more general expression, relating pressure to changes in unfrozen water content of cells, can be given by:…”
Section: Theory a N D Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that negative pressures are likely to occur during only extracellular freezing in the cells, hence the use of term L,, in the above expression. However, in many tissues E is not likely to be constant (Cheung et al, 1976) and thus a more general expression, relating pressure to changes in unfrozen water content of cells, can be given by:…”
Section: Theory a N D Calculationsmentioning
confidence: 99%
“…Henderson and Speedy (1987) also noted that cavitation of water at low temperatures was often associated with spontaneous ice formation, which may result in lethal injury to cells. Studies have shown that stretched water under even small tension can lead to cavitation in plant cells at room temperature (Tyree andDixon, 1983, 1986). …”
Section: Cell Tensionmentioning
confidence: 99%
“…As a result, such species can maintain a positive 4,,, despite decreasing P. Regulation of tissue solute concentation, generally termed osmotic adjustment, has been considered an important mechanism by which higher plants can adapt to increasing salinity (8,16). In species that have been shown to adjust osmotically, maximum 4,6 in salinized plants has often been found to be higher than in nonsalinized plants (1,2,9,11).…”
mentioning
confidence: 99%
“…lowering the minimum possible f), 4 3Abbreviations: *, water potential; 4', osmotic potential; 4,,, turgor potential; E, volumetric bulk modulus of elasticity; OWC, osmotic water content; P, pressure; V, volume; PPFD, photosynthetic photon flux density.…”
mentioning
confidence: 99%
See 1 more Smart Citation